Generalized Metric Spaces Do Not Have the Compatible Topology - Tomonari Suzuki (Abstract and Applied Analysis)
We study generalized metric spaces, which were introduced by Branciari (2000). In particular, generalized metric spaces do not necessarily have the compatible topology. Also we prove a generalization of the Banach contraction principle in complete generalized metric spaces.